Anticoagulation for non-valvular atrial fibrillation: new anticoagulant agents - KEPEZ, ALPER; ERDOĞAN, OKAN (TURKISH SOC CARDIOLOGY, 2013)
Atrial fibrillation (AF) is a common cardiac arrhythmia and it is associated with systemic thromboembolism. Until recently, vitamin K antagonists (VKA) such as warfarin were the only available oral anticoagulant therapy for prevention of stroke and systemic embolism in AF. Limitations of VKA therapy have prompted researchers to search for novel anticoagulant drugs, which do not necessitate coagulation monitoring due to their more predictable pharmacokinetic profile. Large-scale phase III trials have been completed for some of these drugs and 'U.S. Food and Drug Administration (FDA) approved dabigatran and rivaroxaban for prevention of systemic embolism in non-valvular AF patients. In this review, we will first focus on pharmacodynamic and pharmacokinetic profiles of these medications and then try to overview clinical trial results. We will also try to mention the current controversies regarding the clinical application of these drugs.
Keywords: Atrial fibrillation; stroke; systemic embolism; anticoagulation; vitamin K antagonists; novel anticoagulant drugs; RANDOMIZED EVALUATION; DABIGATRAN ETEXILATE; ORAL ANTICOAGULANTS; STROKE PREVENTION; SUBGROUP ANALYSIS; WARFARIN; THERAPY; RISK; MANAGEMENT